Socjalizacyjna funkcja szkolnictwa w Afryce Południowej w okresie apartheidu (1948-1994) - Gmerek, Tomasz (Studia Edukacyjne, 2020)
The article is devoted to the discussion of socialization processes in the South African apartheid sysem of education (1948-1994). The socialization function of education is considered in-depth, with special attention paid to the racial inequality and discrimination in South African society. The article includes the consideration of school indoctrination and different aims of education and curricula in education subsystems for different racial groups in an Apartheid society.